Meso‐Alkynyl BODIPYs: Structure, Photoproperties, π‐Extension, and Manipulation of Frontier Orbitals. Issue 4 (4th February 2013) - Kusaka, Shinpei; Sakamoto, Ryota; Kitagawa, Yasutaka; Okumura, Mitsutaka; Nishihara, Hiroshi
<x xml:space="preserve">Abstract</x> Bodipy building: meso‐Alkynyl BODIPY monomers and dimers were synthesized and their crystal structures, photochemical properties, and electronic structures disclosed. The meso‐arylethynyl group is coplanar with the BODIPY core. The resulting efficient π‐conjugation red‐shifts the intense absorption and bright fluorescence by about 40–70 nm. Cyclic voltammetry and DFT calculations revealed that the LUMO level is stabilized by meso‐alkynylation, while the HOMO level remains constant.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>